2014
DOI: 10.1371/journal.pone.0108383
|View full text |Cite
|
Sign up to set email alerts
|

Improving Mycobacterium bovis Bacillus Calmette-Guèrin as a Vaccine Delivery Vector for Viral Antigens by Incorporation of Glycolipid Activators of NKT Cells

Abstract: Recombinant Mycobacterium bovis bacillus Calmette-Guèrin (rBCG) has been explored as a vector for vaccines against HIV because of its ability to induce long lasting humoral and cell mediated immune responses. To maximize the potential for rBCG vaccines to induce effective immunity against HIV, various strategies are being employed to improve its ability to prime CD8+ T cells, which play an important role in the control of HIV infections. In this study we adopted a previously described approach of incorporating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 50 publications
0
19
0
1
Order By: Relevance
“…Our analysis also took advantage of a hCD1d KI mouse model, which more faithfully replicates many of the features of human i NKT cell responses in comparison to standard wild type mice (Venkataswamy et al, 2014; Wen et al, 2015; Wen et al, 2013). This mouse strain was generated by replacing the mouse genomic segment containing the exons encoding mCD1d with the homologous human genomic sequence (Wen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analysis also took advantage of a hCD1d KI mouse model, which more faithfully replicates many of the features of human i NKT cell responses in comparison to standard wild type mice (Venkataswamy et al, 2014; Wen et al, 2015; Wen et al, 2013). This mouse strain was generated by replacing the mouse genomic segment containing the exons encoding mCD1d with the homologous human genomic sequence (Wen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, in studies using cell culture models of human i NKT cell responses, α- C -GalCer has been found to be only weakly stimulatory, suggesting that it may not be suitable for development as a human therapeutic (Li et al, 2009a; Li et al, 2009b; Venkataswamy et al, 2014). Another strongly Th1-biasing i NKT cell agonist that was previously identified is the aminodiol (sphinganine) analogue (AH03-1 in Figure 1A) of KRN7000, which has activities similar to α- C -GalCer in mouse models (Arora et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…When stimulated with the agonistic lipid α-galactosylceramide (αGalCer), they rapidly secrete high amounts of several cytokines, and there is growing interest in exploiting αGalCer as an immunological adjuvant (Carreno et al, 2014; Singh et al, 2014; Venkataswamy et al, 2014). iNKT cells also secrete cytokines at steady state and early after infection to influence the development and activation of surrounding immune cells (Engel and Kronenberg, 2014; Lee et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Examples include Salmonella spp . [24–26]*, Mycobacterium bovis [27], Listeria monocytogenes [2830], Vibrio cholera [31], Lactobacillus spp. [32], Staphylococcus spp.…”
Section: Delivery Technology To Enhance Vaccination Effectivenessmentioning
confidence: 99%